2020
DOI: 10.5858/arpa.2020-0467-sa
|View full text |Cite
|
Sign up to set email alerts
|

Transition From a Standard to a Hybrid On-Site and Remote Anatomic Pathology Training Model During the Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: Context: As teaching hospitals institute social distancing and defer non-emergent procedures to cope with the coronavirus disease 2019 (COVID-19) pandemic, the need for daily onsite presence, unless necessary has been reduced for all medical staff including trainees. Pathology training programs must adapt to these changes to ensure overall safety without significantly compromising training and educational mission of the institution. Objective: To describe the hybrid on-site and remote anatomic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 5 publications
(5 reference statements)
0
26
0
2
Order By: Relevance
“…The findings confirmed the value of using blended/hybrid learning as the training was well-received and for which the participants expressed a clear preference. Similarly, Guiberson et al (2015) provided preliminary evidence on the effectiveness of a hybrid telehealth model in screening language development in children, while Chin et al (2021) concluded that the hybrid curriculum is an innovative way to maximize learning opportunities while maintaining social distancing in the COVID-19 pandemic era.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings confirmed the value of using blended/hybrid learning as the training was well-received and for which the participants expressed a clear preference. Similarly, Guiberson et al (2015) provided preliminary evidence on the effectiveness of a hybrid telehealth model in screening language development in children, while Chin et al (2021) concluded that the hybrid curriculum is an innovative way to maximize learning opportunities while maintaining social distancing in the COVID-19 pandemic era.…”
Section: Resultsmentioning
confidence: 99%
“…Students agree that it could improve clinical interest while meeting the expected learning outcomes. Chin et al (2021) Transition from a standard to a hybrid on-site and remote anatomic pathology training model during the Covid-19 pandemic. 28 clinical fellows, 35 clinical Faculty, and 22 research fellows participated in this study.…”
Section: Studies Examined Contexts and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social confinement have brought learning inequalities to the spotlight with the lack of access to digital equipment and fear of contagion [6].…”
Section: Health Teaching and Learning In Times Of Pandemicsmentioning
confidence: 99%